Romantic Idealism and Nationalism—Two Important Components of Juozas Tumas-Vaižgantas’s Worldview - Vanagaitė, Gitana (Colloquia, 2020)
The worldview of Juozas Tumas-Vaižgantas, who lived, worked, and created at the end of the 19th century and in the early 20th century, has not been discussed as a separate theme. Researchers have singled out and extensively analyzed Vaižgantas’s nationalism, his commitment to national culture, social involvement, and synthetic nature of his notions and artistic styles. They have not discussed the preconditions for the formation of Vaižgantas’s worldview, its components and the various connections among them, systems and similar questions. Therefore, the article, based on the concept of worldview as human relationship with existence and the world, attempts to define two significant but not the only components of Vaižgantas’s worldview: romantic idealism and nationalism. It does not analyze the ‘ideal of religion’, which was guiding all Vaižgantas’s public and private activities, as it would require a separate study. In this article, the idealism and nationalism discussed in various sources are analyzed as components that establish a certain system of views, i.e., a worldview. The components of Vaižgantas’s worldview discussed in this article are based on his autobiographical sketch, “From Autobiography. My Turbulent Age,” a theoretical article, “Romantic Idealism Returns,” and a conspectus “A Review and Reviewers” from the lectures on the Lithuanian literature during the press ban. The article on romantic idealism, which seems to discuss the literary movement in Lithuanian literature, actually focuses on more general issues, which belong to the sphere of views, understood as a system of views about the world and a certain paradigm of thinking. In his article, Vaižgantas especially emphasizes the importance of an idealistic worldview for the progress of the human spirit and for the future of humanity as a whole. Nationality, the second component of Vaižgantas’ worldview, which is more broadly discussed in his lectures on the Lithuanian press ban and man‘s duty to the country that had formed because of it, belongs to the same sphere of ideals. Guided by the ideal of nationality, Vaižgantas chose to be a priest. This ideal became an imperative of his entire life—to serve the freedom and culture of the nation.